2017
DOI: 10.1037/abn0000246
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of pregnancy and postpartum depressive symptoms: Latent class trajectories and predictors.

Abstract: Depressive symptoms among pregnant and postpartum women are common. However, recent studies indicate that depressive symptoms in the perinatal period do not follow a uniform course, and investigations of the heterogeneity of time courses and associated factors are needed. The aim of this study was to explore whether depressive symptoms in the perinatal period could be categorized into several distinct trajectories of symptom development among subgroups of perinatal women, and to identify predictors of these tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 50 publications
9
62
0
Order By: Relevance
“…As noted above, the primary approach taken in studies in this area to date has been to test the hypothesis that levels of RNT reported in the antenatal period predict poor psychological adjustment in the post-partum period. However, the identification of distinct classes of postnatal depressive symptom trajectories (e.g., depressive symptoms in pregnancy only, post-partum symptoms only, symptoms that persist from pregnancy to the post-partum period [35]), coupled with findings that RNT predicts postnatal depression only in combination with other factors (e.g., perfectionism [28]; social functioning [27]), suggests that a relatively linear account of pre-birth RNT serving as a risk factor for developing postnatal depression and anxiety may not capture the clinical reality for all women who experience post-partum psychological symptoms.…”
Section: Potential Roles Of Rnt In the Perinatal Contextmentioning
confidence: 99%
“…As noted above, the primary approach taken in studies in this area to date has been to test the hypothesis that levels of RNT reported in the antenatal period predict poor psychological adjustment in the post-partum period. However, the identification of distinct classes of postnatal depressive symptom trajectories (e.g., depressive symptoms in pregnancy only, post-partum symptoms only, symptoms that persist from pregnancy to the post-partum period [35]), coupled with findings that RNT predicts postnatal depression only in combination with other factors (e.g., perfectionism [28]; social functioning [27]), suggests that a relatively linear account of pre-birth RNT serving as a risk factor for developing postnatal depression and anxiety may not capture the clinical reality for all women who experience post-partum psychological symptoms.…”
Section: Potential Roles Of Rnt In the Perinatal Contextmentioning
confidence: 99%
“…LiN is an ongoing Norwegian longitudinal project (cf. Skjothaug, Smith, Wentzel‐Larsen, & Moe, ; Fredriksen, von Soest, Smith & Moe, ). The study is community‐based with a prospective cohort design, investigating pre‐ and postnatal risk and promotive factors influencing early child development and mental health.…”
Section: Methodsmentioning
confidence: 99%
“…Attrition analysis for the mothers in the LiN study is reported in Fredriksen et al. (). Briefly, 50.7% of the mothers consented at the four well‐baby clinics where this was reliably recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Both pregnancy-related anxiety and previous psychopathology have been observed to be associated with the occurrence of depressive symptoms among pregnant and postpartum women [1, 2]; however, some kinds of intervention have been reported to reduce the relapse/deterioration of depressive symptom during pregnancy and postpartum [3, 4]. Recently, some oriental treatments such as acupressure (Shiatsu), acupuncture and moxibustion have seemed to be an effective optional treatment in patients with depression [5-9].…”
Section: Introductionmentioning
confidence: 99%